Faktor-Faktor Yang Mempengaruhi Permintaan Sayur Pada Konsumen Rumah Tangga di Kecamatan Lawa Kabupaten Muna Barat - Asmarita, Eganing; Rianse, Ilma Sarimustaqiyma; Sadimantara, Fahria Nadiryati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the demand for and the factors that influence the demand for vegetables in households in Lawa District, West Muna Regency. Determination of the sample was carried out using the simple random sampling method so that the number of samples found was 96 respondents. Variables observed: Respondent's identity includes age, education level, number of family dependents and income and the dependent variable includes demand for vegetables.The results showed that: The demand for vegetables in households in Lawa District, West Muna Regency, consumed an average of 4 kg of vegetables with an average frequency of consumption of vegetables 12 times a month and the factors that influence the demand for vegetables in households in Lawa Subdistrict, West Muna Regency were the price of vegetables, the price of tempeh/tofu, the price of eggs, the price of chicken meat, the price of fish, the number of family members, and family income. The results of the t-test analysis showed that only the price of eggs and the number of family members had a significant effect on the demand for vegetables